2006
DOI: 10.1038/sj.onc.1209785
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in malignant glioma cells triggered by the temozolomide-induced DNA lesion O6-methylguanine

Abstract: Methylating drugs such as temozolomide (TMZ) are widely used in the treatment of brain tumours (malignant gliomas). The mechanism of TMZ-induced glioma cell death is unknown. Here, we show that malignant glioma cells undergo apoptosis following treatment with the methylating agents N-methyl-N 0 -nitro-N-nitrosoguanidine (MNNG) and TMZ. Cell death determined by colony formation and apoptosis following methylation is greatly stimulated by p53. Transfection experiments with O 6 -methylguanine-DNA methyltransferas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
405
4
13

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 448 publications
(448 citation statements)
references
References 57 publications
26
405
4
13
Order By: Relevance
“…Similarly, p53 was shown to function as a survival factor in the gastrointestinal tract under conditions of severe irradiation, which was attributed to increased sensitivity of vascular endothelial cells (Komarova et al, 2004;Burdelya et al, 2006). Furthermore, other reports have identified conditions in which absence of p53 led to elevated apoptosis, but a direct causal role for p53 in providing survival signals has not been described (Lassus et al, 1996;Lackinger and Kaina, 2000;Hermisson et al, 2006;Batista et al, 2007;Roepke et al, 2007;Roos et al, 2007). Notwithstanding these occasional reports, the major observations that p53 activation often leads to apoptosis or DNA repair have been overwhelming, and hence, have overshadowed the exploration of the survival-promoting properties of p53.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, p53 was shown to function as a survival factor in the gastrointestinal tract under conditions of severe irradiation, which was attributed to increased sensitivity of vascular endothelial cells (Komarova et al, 2004;Burdelya et al, 2006). Furthermore, other reports have identified conditions in which absence of p53 led to elevated apoptosis, but a direct causal role for p53 in providing survival signals has not been described (Lassus et al, 1996;Lackinger and Kaina, 2000;Hermisson et al, 2006;Batista et al, 2007;Roepke et al, 2007;Roos et al, 2007). Notwithstanding these occasional reports, the major observations that p53 activation often leads to apoptosis or DNA repair have been overwhelming, and hence, have overshadowed the exploration of the survival-promoting properties of p53.…”
Section: Discussionmentioning
confidence: 99%
“…For example, absence of p53 has been shown to promote taxol-mediated death owing to failure of cell arrest in the G 1 phase of the cell cycle, and hence, allowing cells to accumulate in the G 2 /M phase where they undergo mitotic cell death (Vikhanskaya et al, 1998). In addition, cells with wild-type p53 have been shown to be more resistant to cytotoxic drug treatment in some cases (Hermisson et al, 2006;Batista et al, 2007;Roos et al, 2007). Other reports have also shown that absence of p53 leads to sensitization to UV irradiation and alkalyting agents in mouse embryonic fibroblasts (MEFs), and to thymoquinone-induced apoptosis in human cells (Lackinger and Kaina, 2000;Roepke et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…the mechanism observed in other cell systems in response to alkylating agents, 24,25 the following marker proteins were assayed: phosphorylated H2AX, p53, p21, Fas/CD95/Apo-1, Bcl-2, Bcl-2-associated X protein (Bax), cytochrome c, active fragments of caspase-7 and caspase-3. As shown in Figure 6, in the nucleus of ES (R1) cells histone H2AX becomes phosphorylated after MNNG treatment, which was was performed using an E2F1-specific antibody.…”
Section: Mechanism Of O 6 Meg-induced Apoptosis In Es Cells To Verifmentioning
confidence: 99%
“…Western blot analysis was performed as described. 25 Antibodies used were anti-P53 and anti-cytochrome c (Oncogene), anti-Fas, antiBcl-2, anti-Bax and ERK2 (Santa Cruz Biotechnology Inc.), anti-caspase-3, anticaspase-7 and anti-phospho-Rb (ser807/811) (Cell Signaling technology), anti-Rb (Pharmingen), MSH2 (Calbiochem) and MSH6 (Transduction Laboratories).…”
Section: Preparation Of Protein Extractsmentioning
confidence: 99%
“…Notably, cells with mutated DNA-PKcs were more sensitive to TMZ-induced apoptosis. Since both p53 wild-type and p53 mutant glioma cells undergo apoptosis in response to TMZ, TP53 is not necessarily required for TMZ-induced apoptosis (Roos et al, 2007). Inhibition of DNA-PKcs may offer a way to improve both the efficiency of TMZ therapy and radiotherapy.…”
Section: Cellular Effects Of Temozolomidementioning
confidence: 99%